Identification and characterization of the TLR18 gene in grass carp (Ctenopharyngodon idella). Issue 2 (December 2015) - Huang, Wen-Ji; Shen, Yubang; Xu, Xiao-Yan; Hu, Mo-Yan; Li, Jia-le
Abstract: Toll-like receptors (TLRs) play a critical role in the innate immune system. Although TLR18 is an important member of this family of receptors in fish, the role of the tlr18 gene in responses to pathogen infection is still unclear. In this study, we identified and characterized the grass carp tlr18 gene ( gctlr18 ) to further clarify the function of TLR18 in teleost fish. Gctlr18 spans over 3600 bp and encodes a polypeptide of 852 amino acids. Analysis of the deduced amino acid sequence showed that gctlr18 encodes structures typical of the TLR family, including a signal peptide, seven leucine-rich repeats (LRRs), a transmembrane region, and a (Toll-interleukin-1 receptor) TIR domain. Quantitative RT-PCR analysis showed that gctlr18 was constitutively expressed in all investigated tissues, with abundant expression in spleen, gill, heart, intestine, kidney and fin and low expression in skin, liver and brain. Following grass carp reovirus-challenge and Aeromonas hydrophila inoculation, gctlr18 transcripts were upregulated significantly in immune-relevant tissues. Stimulation of Ctenopharyngodon idella kidney (CIK) cells with purified flagellin from Salmo typhimurium, lipopolysaccharide and polyinosinic-polycytidylic acid stimulation in vitro resulted in significantly increased gctlr18 expression, reaching a peak followed by restoration of normal levels. Overexpression of gctlr18 reduced A. hydrophila invasion by 83.4%. In CIK cells, gctlr18 induced the expression of proinflammatory cytokines, including il-8, inf-1 and tnf-α . Our results indicate that gctlr18 plays a key role in innate immune responses in teleost fish. Highlights: We characterized tlr18 gene expression in grass carp in vivo and CIK cells in vitro . Viral and bacterial challenge upregulated gctlr18 in immune-relevant tissues. Overexpression of tlr18 inhibited Aeromonas hydrophila infection. Overexpression of tlr18 induced il-8, ifn and tnf-α expression via the NF-κB pathway.